PENGARUH UKURAN PERUSAHAAN, LIKUIDITAS DAN JATUH TEMPO OBLIGASI TERHADAP TINGKAT SEWA SUKUK IJARAH PADA PERUSAHAAN YANG MENERBITKAN SUKUK IJARAH DI BURSA EFEK INDONESIA PERIODE 2015-2019 - Fahrul Alam Masruri; Monica Esa Yan Khikmah (Universitas Widyatama, 2020)
The phenomenon of sukuk ijarah that gives a return that remains more in demand than sukuk mudharabah. This study aims to determine the influence of Company Size, Liquidity and Bond Maturity on Sukuk Ijarah Rental Rate on Companies Issuing Sukuk Ijarah on the Indonesia Stock Exchange for the period 2015-2019. The research method used is quantitative method with Multiple Linear Regression model and data processing using SPSS 25. The sampling technique in the study was saturated sampling. Companies that issue Sukuk Ijarah on the Indonesia Stock Exchange for the period 2015-2019 are used as samples. The results showed that the size of the company had no partial effect on the sukuk ijarah rental rate, liquidity proved to have a positive and significant effect on sukuk ijarah rental rate, bond maturity had a negative and significant effect on sukuk ijarah rental rate. Meanwhile, empirically, it is proven that the size of the company, liquidity and maturity of bonds simultaneously affect the rental rate of sukuk ijarah in companies listed on the Indonesia Stock Exchange for the period 2015-2019